2022
DOI: 10.1039/d2ta03720c
|View full text |Cite
|
Sign up to set email alerts
|

Modulating surface charges of bismuth tantalum oxychloride nanoplates for promoting photogenerated charge separation

Abstract: Modulation of anisotropic facets and surface charge properties of semiconductor photocatalysts play significant roles in accelerating the photogenerated charge separation in heterogeneous photocatalysis. Herein, taking Bi4TaO8Cl (BTOC) as an exemplar,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…41 Besides, surface pretreatment under different pH conditions also allows the selective loading of cocatalysts on the different facets of Bi 4 TaO 8 Cl. 42 Given the decent performance of Bi 4 MO 8 X (M = Nb, Ta, X = Cl, Br) towards photocatalytic water oxidation, Z-scheme overall water splitting systems using Bi 4 MO 8 X as oxidation photocatalysts have been demonstrated widely. The simultaneous evolution of H 2 and O 2 with a stoichiometric ratio demonstrate the successful achievement of overall water splitting, presenting a promising candidate for solar energy conversion.…”
Section: Modulation Of Crystal Structuresmentioning
confidence: 99%
“…41 Besides, surface pretreatment under different pH conditions also allows the selective loading of cocatalysts on the different facets of Bi 4 TaO 8 Cl. 42 Given the decent performance of Bi 4 MO 8 X (M = Nb, Ta, X = Cl, Br) towards photocatalytic water oxidation, Z-scheme overall water splitting systems using Bi 4 MO 8 X as oxidation photocatalysts have been demonstrated widely. The simultaneous evolution of H 2 and O 2 with a stoichiometric ratio demonstrate the successful achievement of overall water splitting, presenting a promising candidate for solar energy conversion.…”
Section: Modulation Of Crystal Structuresmentioning
confidence: 99%
“…By utilizing these features, the reaction site of reduction and oxidation can be separated in different planes, by modifying the synthesis and the way of loading cocatalysts. 152–154…”
Section: Other Issuesmentioning
confidence: 99%
“…To our surprise, all of the doping systems at DMAP show a longer lifetime and weaker phosphorescence intensity, while all of the doping systems at ISO2Cz feature a shorter lifetime and higher phosphorescence intensity (Figure b). On carefully analyzing the single crystals of two matrixes (Figures S46–S47), we found that resemblant chemical structures of guests and ISO2Cz enable them to approach each other and interact with each other via a variety of interactions, thus facilitating the charge separation (CS) and charge recombination (CR) process. The HOMO-LUMO energy levels of the guest match well with the ones of ISO2Cz, which significantly promotes the efficiency of the CS and CR process. To our best knowledge, this work is a systematic study on how matrixes influence the RTUOP of guest-matrix doping systems and may give deep insight into the development of organic phosphorescence.…”
Section: Introductionmentioning
confidence: 96%